Developing an Innovative Environmental Accounting Model to Support the Achievement of Sustainable Development Goals (SDGs) - Putri Estiarto, Lintang; Suraji, Robertus; Istianingsih, Istianingsih; Ali, Hapzi (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2023)
This research aims to explore the role of innovative environmental accounting practices in supporting carbon mitigation efforts and achieving Sustainable Development Goals (SDGs). Through a qualitative approach, this research examines the implementation of environmental accounting practices, such as carbon footprint measurement, environmental cost accounting, and sustainability reporting, within organizations. The findings indicate that environmental accounting practices positively contribute to carbon mitigation efforts and the achievement of SDGs, particularly goals related to clean and affordable energy, responsible consumption and production, and climate action. However, the research also identifies some challenges in implementing these practices, including resource limitations and the complexity of measuring environmental impacts. These findings emphasize the importance of integrating environmental accounting practices into overall organizational strategies and the need for cross-sector cooperation to address challenges in their implementation. This research makes an important contribution to the environmental accounting literature and offers valuable insights for practitioners, academics, standard setters, and related professional associations in developing and implementing effective environmental accounting practices to support environmental and social sustainability.